Prevalence of Theileria orientalis types in beef cattle herds on the North Coast of New South Wales. Issue 4 (April 2016) - Proctor, AKK; Ball, M; Freeman, P; Jenkins, C; Bogema, DR
Abstract : Objective: To estimate the prevalence of Theileria orientalis infection for Chitose, Ikeda and Buffeli major piroplasm surface protein (MPSP) types at a herd‐ and animal‐level in beef cattle in the North Coast Livestock Health and Pest Authority (NCLHPA) region of New South Wales (NSW). Methods: A total of 24 beef herds in the NCLHPA region containing more than 100 cattle were randomly selected. Blood samples were collected from five animals per herd and tested using Theileria PCR for Chitose, Buffeli and Ikeda. Samples were only taken from female cattle older than 2 years, born in the NCLHPA region and apparently healthy at the time of testing. Results: The herd‐level prevalence for all MPSP types (Chitose, Ikeda and Buffeli) was 100%, with a 95% confidence interval of 86.3–99.9%. The mean prevalence at an animal level was 83.3%, 92.5% and 95.0% for Theileria Chitose, Buffeli and Ikeda, respectively. Quantitative PCR testing showed that 81.9% of animals had a low‐level infection, while 17.0% had a moderate level of infection, and only 1.0% had a high level of infection. The majority of animals had a mixed infection of two or three MPSP types and few animals showed single infection. Conclusion: The results indicate endemicity of T. orientalis, especially the Ikeda type, in the NCLHPA region of Australia.